2018
DOI: 10.1155/2018/2653497
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Comparisons of Volumetric Modulated Arc Therapy and Tomotherapy for Early T-Stage Nasopharyngeal Carcinoma

Abstract: Purpose To compare the dosimetric differences between volumetric modulated arc therapy (VMAT) and helical tomotherapy (HT) in treating early T-stage nasopharyngeal carcinoma (NPC). Method Ten patients with early T-stage NPC who received tomotherapy using simultaneously integrated boost (SIB) strategies were replanned with VMAT (RapidArc of Varian, dual-arc). Dosimetric comparisons between the RapidArc plan and the HT plan included the following: (1) D98, homogeneity, and conformity of PTVs; (2) sparing of orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 39 publications
5
20
0
Order By: Relevance
“…The difference between both studies using the same radiation protocol is difficult to determine but it could be because of a difference in calculation algorithm that may contribute to a difference in LG dose but the delivery systems are vastly different and that would probably result in a more significant difference. It is well recognized that IMRT/IGRT treatment using a TomoTherapy machine often leads to a better sparing of normal tissue . There is also the possibility that the contours used in the TomoTherapy study were more conservative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The difference between both studies using the same radiation protocol is difficult to determine but it could be because of a difference in calculation algorithm that may contribute to a difference in LG dose but the delivery systems are vastly different and that would probably result in a more significant difference. It is well recognized that IMRT/IGRT treatment using a TomoTherapy machine often leads to a better sparing of normal tissue . There is also the possibility that the contours used in the TomoTherapy study were more conservative.…”
Section: Discussionmentioning
confidence: 99%
“…It is well recognized that IMRT/IGRT treatment using a TomoTherapy machine often leads to a better sparing of normal tissue. 18,19 There is also the possibility that the contours used in the TomoTherapy study were more conservative. Furthermore, the bolus used in our cases will inherently result in more superficial dose regardless of optimization and IMRT delivery.…”
Section: Discussionmentioning
confidence: 99%
“…FF-IMRT and VAMT contribute greatly in radiotherapy, followed by HT, a neo-CT based rotational IMRT, which provides better OARs sparing with 51 independent beam directions, delivers a highly conformal dose distribution. Nowadays, HT is frequently used for a variety of diseases [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…BioMed Research International three groups were far lower than the limit of 54 Gy. Li et al [31] analyzed dosimetric differences between VMAT and HT for early T-stage nasopharyngeal carcinoma and found that VMAT showed significant superiority in sparing the optic nerves and optic chiasm. This is in line with our study.…”
mentioning
confidence: 99%